Acute adverse events associated with the administration of Crotalidae polyvalent immune Fab antivenom within the North American Snakebite Registry. (2nd November 2018) - Kleinschmidt, Kurt; Ruha, Anne-Michelle; Campleman, Sharan; Brent, Jeffrey; Wax, Paul
Abstract: Background: Crotalidae Polyvalent Immune Fab (Fab Antivenom) is the primary Viperid antivenom used in the United States since 2000. Adverse event data associated with its use are limited. The purpose of this study is to describe the prevalence of acute adverse events associated with the use of Fab antivenom. Methods: The American College of Medical Toxicology's Toxicology Investigators Consortium maintains a prospective case registry of poisoned and envenomated patients managed by medical toxicologists at the bedside. This registry includes the North American Snakebite sub-registry. We performed a review of 438 cases entered into the Snakebite sub-registry. Results: A total of 373 (85.2%) received at least one vial of Fab Antivenom. Forty percent were children. Adverse events occurred in 10 patients (2.7%) of whom six were adults. Rash was the most common adverse event. More severe adverse events (hypotension, bronchospasm, and/or angioedema) occurred in four (1.1%) patients. Prophylaxis was administered prior to Fab antivenom in 4.0%. Eight patients received various treatments for their adverse events. Neither the initial number of Fab antivenom vials, atopic history, nor prior envenomation correlated with the prevalence of adverse events. Discussion: This prevalence of adverse events was lower than in previous studies and in a meta-analysis of 11 studies. The types of adverse events and treatments used are consistent with those in previous reports. There were no prior reports of prophylaxis use with which to compare. Conclusion: The prevalence of Fab antivenom adverse events in the North American Snakebite Registry was 2.7%.